1964
DOI: 10.1161/01.cir.29.5.680
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Stenosis of the Pulmonary Artery Branches

Abstract: CONGENITAL stenosis of the pulmonary artery branches is an anomaly characterized by narrowed segments of one or more of the main or peripheral branches of the pulmonary artery. Such conditions lhave been variously labeled pulmonary coaretation,' peripheral pulmonary stenosis,2 and multiple peripheral stenoses 3 of the pulmonary artery. Several cases of this anomaly have appeared in the literature 1-17 since its first description by Oppenheimer4 in 1938. The problems produced by stenosis of the branches of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…The murmur usually disappears by 3-6 months of age. If a murmur persists beyond this age with the same Doppler characteris tics, a structural narrowing of the pulmonary artery tree (peripheral pulmonary artery ste nosis) should be suspected [9][10][11].…”
Section: Functional Murmur and Echocardiographymentioning
confidence: 99%
“…The murmur usually disappears by 3-6 months of age. If a murmur persists beyond this age with the same Doppler characteris tics, a structural narrowing of the pulmonary artery tree (peripheral pulmonary artery ste nosis) should be suspected [9][10][11].…”
Section: Functional Murmur and Echocardiographymentioning
confidence: 99%
“…The azygous vein group was privileged be cause of special interest in this autologous material, and provided 3 animals. 4 5-7 months postoperatively, but 1 already had a rather severe stenosis. It must be em phasized that there was no significant aggra vation during a further 9-month (average) follow-up (table V).…”
Section: Resultsmentioning
confidence: 95%
“…Momma et al [23], in an angiographic study, found nine cases of juxtaductal LPA stenosis and five cases of juxtaductal LPA atresia. Baum et al [1], in a clinicoradiologic study, reported 26 cases of pulmonary arterial branch stenoses. However, the exact sites of the pulmonary stenoses were not described.…”
Section: Discussionmentioning
confidence: 99%